2023
DOI: 10.1038/s41467-023-36736-1
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical graph learning for protein–protein interaction

Abstract: Protein-Protein Interactions (PPIs) are fundamental means of functions and signalings in biological systems. The massive growth in demand and cost associated with experimental PPI studies calls for computational tools for automated prediction and understanding of PPIs. Despite recent progress, in silico methods remain inadequate in modeling the natural PPI hierarchy. Here we present a double-viewed hierarchical graph learning model, HIGH-PPI, to predict PPIs and extrapolate the molecular details involved. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 67 publications
1
31
0
Order By: Relevance
“…7 Among them, adsorption has the advantages of economical and easy separation in terms of cost and recovery and has been widely used for metal recovery. 8,9 Shao et al 10 reported a strategy for the closed-loop recovery of Ag + using amorphous mixed-valence MoO x . MoO x exhibited an ultrahigh capture capacity (2605.91 mg g À1 ) and excellent selectivity for Ag + .…”
Section: àmentioning
confidence: 99%
“…7 Among them, adsorption has the advantages of economical and easy separation in terms of cost and recovery and has been widely used for metal recovery. 8,9 Shao et al 10 reported a strategy for the closed-loop recovery of Ag + using amorphous mixed-valence MoO x . MoO x exhibited an ultrahigh capture capacity (2605.91 mg g À1 ) and excellent selectivity for Ag + .…”
Section: àmentioning
confidence: 99%
“…For example, edges corresponding to chemical bonds can guide a model toward learning chemical knowledge more rapidly or with less data than would otherwise be needed. Graph neural network (GNN) architectures have recently achieved state-of-the-art performance in multiple protein-related tasks, as exemplified by the DeepFRI and HIGH-PPI methods for predicting protein function and protein–protein interactions, respectively. Special graph-based protein representations, such as point clouds (no edges) or complete graphs (a full set of edges), are especially convenient for processing using powerful transformer models. , …”
Section: Principles Of Machine Learningmentioning
confidence: 99%
“…14,15 Among the ones listed above, adsorption is an effective, easy-to-design, and cost-effective process for wastewater treatment. 16,17 It occurs at the interface between liquid and solid phases, transporting antibiotics to solid matrices like the soil, sediments, and plants. 18 For the successful removal of antibiotics from aquatic environments, several adsorbents have been created, including multiwalled carbon nanotubes, 19 nanofibers, 20,21 activated carbons, 22 zeolites, 23 cyclodextrin polymers, 24 and clay.…”
Section: Introductionmentioning
confidence: 99%